The Impact of Personal Gender-Typicality and Partner Gender-Traditionality on Taking Sexual Initiative: Investigating a Social Tuning Hypothesis - Emmerink, Peggy M. J.; Van Den Eijnden, Regina J. J. M.; Ter Bogt, Tom F. M.; Vanwesenbeeck, Ine (Frontiers in Psychology, 2017)
Sexual assertiveness is an issue of interest in the context of gender equality and sexual health. This study investigated the social tuning hypothesis that encountering a gender-traditional partner would lead to stronger gender-typical behaviour, i.e. respectively higher and lower levels of taking sexual initiative among men and women. Participants (N=271) read a vignette describing a romantic partner, who was either presented as gender-traditional or not, followed by a sexual scenario. Subsequently, participants were asked about their expectations towards their own sexual initiative taking. Results showed a significant ‘target gender-traditionality x participant gender x participant gender-typicality (masculinity/femininity)’ interaction meaning that less gender-typical men were more likely to initiate sexual contact in the experimental, compared to the control condition. Men low in masculine characteristics showed higher initiative taking in response to a gender-traditional target female. We conclude that less gender-typical men seem to employ more social tuning towards their sexual partner, whereas more gender-typical men seem to adhere to their gender-typical behaviour regardless of perceived partner characteristics. These results were not seen among the women in the sample. These findings are a starting point for the further development of experimental investigations regarding the gendered nature of both sexual initiative taking and sexual assertiveness in general.